(untitled) (Third Sector Social Economic Review, 2022)
The aim of this study is to investigate whether the intense stress levels perceived by adults between the ages of 18-65 are predicted by transactional analysis life positions during the Covid-19 pandemic period. Relational survey method, one of the quantitative research methods, was used in the study. The study group of the research consists of 502 adults between the ages of 18-65. Of the adults participating in the research, 63.5% (n=319) are female and 36.5% (n=183) are male. Life Positions Scale and Intense Stress Scale were used as data collection tools in the study. As a result of the study, there were a negative and low level between the perceived intense stress level and the ""I am OK, You are OK"" position(healthy position), the positive and very low level between the ""I am not OK, You are OK"" position(depressive position), and positive and low level significant relationships between the ""I am not OK, You are not OK” position(unhealthy position). As a result of the multiple linear regression analysis, it was found that three of the life positions were a significant predictor of the intense stress perceived together. These three life positions explain 16% of the intense stress perceived by individuals between the ages of 18-65 during the Covid-19 period.